Studi Transposisi Didaktik Internal pada Materi Qirā’ah Kelas VII MTs Negeri 13 Ciamis: Transposisi Didaktis Internal dalam Materi Pembelajaran Qirā’ah - Ima Maryatul Ulpah; Hikmah Maulani; Zahra Alawiyah Rofieq (Language Development Center, 2026)
Background: Reading is a complex language activity involving the recognition of linguistic symbols, cognitive processing, and interpretation of textual meaning, making qirā’ah an essential skill in Arabic language learning. In this context, internal didactic transposition is the process by which teachers transform instructional materials into more accessible and meaningful classroom learning experiences. Purpose: This study aims to describe and analyze the forms and strategies of material adaptation in qirā’ah instruction while examining the role of internal didactic transposition in classroom practices. Method: This research employed an interpretive qualitative approach with a phenomenological design. Data were collected from curriculum and teaching module documents as well as interviews with an Arabic language teacher selected through purposive sampling. The data were analyzed using praxeological document analysis and thematic analysis, supported by source and method triangulation. Result and Discussion: The results indicate no conceptual gap between the curriculum and the teaching modules in terms of learning outcomes and reading competencies. However, teaching methods are not explicitly defined, causing reading comprehension and grammatical analysis activities to rely heavily on teachers’ pedagogical initiatives, implemented through explanations, translation, and contextual examples in the classroom. These findings indicate that internal didactic transposition occurs through teachers’ pedagogical adaptations in classroom practice. Conclusions and Implications: The novelty of this study lies in demonstrating that internal didactic transposition not only occurs at the planning level but is also significantly mediated by teachers’ pedagogical practices in qirā’ah instruction. Internal didactic transposition plays a crucial role in bridging the gap between curriculum design and classroom implementation. These findings suggest that the effectiveness of learning depends not only on the quality of instructional materials but also on their clarity and structure in supporting classroom practices. Therefore, textbooks written entirely in Arabic should provide clearer instructions and more structured reading activities to support students with varying levels of proficiency.